The congruence between the preferred and actual places of death among terminal cancer patients in China - Lin, Huijing; Ni, Ping; Wu, Bei; Liao, Jing; Fu, Jie (Frontiers in Psychology, 2024)
Background: Dying in preferred place is important for good death. Nowadays, no study has evaluated the extent to which the preferences for the place of death (PoD) are met among terminal cancer patients in China. This study examined the congruence between the preferred and actual PoD and its predictors among terminal cancer patients in China.Methods: Between 2015 and 2023, 845 terminal cancer patients from four tertiary hospitals in Wuhan, China were enrolled and followed till death. Face-to-face survey at baseline and telephone-based interviews in the last month of patients' life were combined to learn patients' preferred PoD. Data on patients' actual PoD was collected from families within one month after patients' death.Results: Among the 410 patients who died, 62.7% of them died in hospitals. The agreement between patients' preferred and actual PoD was fair (𝜅=0.221). The congruence between patients' preferred and actual PoD were 63.0%, 36.6% and 0 for hospital death, home death, and hospice facility/nursing home death separately. Patients were more likely to die in their preferred places if their preferred place and family caregivers' belief of patients' preferred PoD was congruent (odds ratio [OR]=6.464, P=0.001), or caregivers had a medical related occupation (OR=4.577, P=0.003); if patients were hospitalized at least twice in the last month of life (OR=0.422, P=0.000), or the quality of care received by patients in the last 48 hours was rated good by the families (OR=0.373, P=0.011), patients were less likely to die in their preferred places.The congruence between patients' preferred and actual PoD was fair. Advance care planning needs to be popularized among China, and the quality of care in hospice facilities and nursing homes should be improved. Necessary policy support for hospice care should be made to respect cancer patients' end-of-life care preferences in mainland China.